Pandemi Covid-19: Refleksi Pentingnya Optimasi Lahan Pekarangan Sebagai Penyokong Kemandirian Pangan Dan Kesehatan Keluarga - Priyaji Agung Pambudi (Universitas Lambung Mangkurat, 2020)
The COVID-19 pandemic was outbreak since January 2020 has now spread out to 213 countries, infected 29,227,348 people and 929,263 deaths. In Indonesia, 221,523 people were infected and 8,841 of them died. Neither the vaccine nor the cure has been found, but the researchers recommend that people consume various types of rhizome plants, moringa, guava, and others as prevention. The opportunity for the Indonesian people to increase their sovereignty in facing the COVID-19 pandemic is very overt because it has a geographical advantage as a tropical country traversed by the equator and fertile soil. This study aims to determine the use of backyards and its importance in promote family health amid the COVID-19 outbreak. This research was conducted in Pacitan Regency, East Java, from March 16 to April 17, 2020 through a qualitative approach with a combined method of questionnaires (162 people), in-depth interviews (18 people), and desk study. The findings showed that 95.06% of respondents agreed that the backyard was an environmental asset, 100% agreed that the backyard could be used to fulfill the needs of vegetables and toga. As 78.4% of respondents have planted vegetables and toga in their backyards and 64.2% feel calmer in facing the COVID-19 pandemic in terms of availability of the need for vegetables and traditional herbal ingredients. This is stated as an ease of concocting traditional herbal medicine and fulfilling kitchen needs for 86.42% of respondents and 57.41% assessed that their families do not depend on market uncertainty because the pattern of backyard use is carried out by growing vegetables and toga plants. The backyard as an environmental asset can promote the realization of food sovereignty (non-rice) and family health if it is managed properly, both flat and vertically.